Differential Use of Food Resources Between the Kelp Gull Larus dominicanus and the Threatened Olrog's Gull L. atlanticus - Yorio, Pablo Martin (2013)
We assessed the potential overlap in diet composition of the kelp gull Larus dominicanus and the threatened Olrog's gull L. atlanticus breeding syntopically at Bahía San Blas, Argentina, during two breeding seasons (2006 and 2007). Diet was studied using regurgitated pellets (180 per species and year) and chick stomach samples obtained through the water offloading technique (60 per species only in 2007). Kelp gulls fed on at least 18 prey types. Fish was the most important diet component (73.3–85%, depending on breeding stage and year), mainly stripped weakfish Cynoscion guatucupa (63.3–75%). Crustaceans were the main prey encountered in Olrog's gull diet, particularly the crabs Neohelice granulata and Cyrtograpsus altimanus, with frequencies of occurrence of over 98% at all breeding stages. Fish in Olrog's gulls diet were only recorded in the old chick stage and in less than 3.3% of samples, while the occurrence of crustaceans in kelp gull diet throughout the study period was never greater than 13%. The specialised crab-based diet of Olrog's gulls contrasts sharply with the generalist and opportunistic diet of the kelp gull. The characteristics of prey remains and the large size of stripped weakfish found in kelp gull diet samples suggest they were obtained from coastal sport and artisanal fisheries. Future studies should monitor the consumption of fish waste by kelp gulls as a function of changes in fishing effort, and assess the dietary overlap between both gull species in coastal sectors where breeding birds have no access to this human-derived food source.